PREFACE: Reformation of Health System in Indonesia - Erfen Gustiawan Suwangto (Review of Primary Care Practice and Education (Kajian Praktik dan Pendidikan Layanan Primer), 2022)
We’re looking forward to reformation era of health sector in Indonesia since the declaration of Perkumpulan Dokter Seluruh Indonesia (Indonesian Doctors Association). The reformation process is starting with ongoing the revision of Medical Practice Act and Medical Education Act.